2008
DOI: 10.28945/439
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Paradigm Development and Course Level on Performance in Technology-Mediated Learning Environments

Abstract: We investigate the effect of paradigm development and course level on the outcomes of web based technology-mediated learning environments in order to ascertain if these external factors can help explain student outcomes. Using an institutional database of student outcomes, we were able to examine data from over 13,000 students in 167 undergraduate courses from the years 1997 -2003. Using this data we examined the question which types of courses are best suited for delivery using web-based technologies. The fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 40 publications
0
15
0
Order By: Relevance
“…More specifically with regard to subject matter effects, Burke and Moore's (2003) conceptualization of Biglan's (1973) subject matter classification scheme suggested differing structures and orientations between Organizational Behavior, Accounting, and Business Computing courses. The topic of paradigm structures in online learning has started to receive research attention, producing inconsistent findings that either hard (Hornik, Saunders, Moskal, & Dziuban, 2003) or soft (Vaverick & Saunders, 1993–1994) paradigm structures were associated with positive course outcomes in online learning and/or satisfaction with online learning. Although this research has been inconclusive, it certainly suggests that there are discipline‐related differences in online learning outcomes.…”
Section: Literature Review and Theory Developmentmentioning
confidence: 99%
“…More specifically with regard to subject matter effects, Burke and Moore's (2003) conceptualization of Biglan's (1973) subject matter classification scheme suggested differing structures and orientations between Organizational Behavior, Accounting, and Business Computing courses. The topic of paradigm structures in online learning has started to receive research attention, producing inconsistent findings that either hard (Hornik, Saunders, Moskal, & Dziuban, 2003) or soft (Vaverick & Saunders, 1993–1994) paradigm structures were associated with positive course outcomes in online learning and/or satisfaction with online learning. Although this research has been inconclusive, it certainly suggests that there are discipline‐related differences in online learning outcomes.…”
Section: Literature Review and Theory Developmentmentioning
confidence: 99%
“…There have also been a few comparative studies. For example, Hornik, Saunders, Li, Moskal & Dzuiban (2008) found that student grades were significantly higher and withdrawal rates were lower for courses in hard disciplines compared to those in soft disciplines in online education. Considering the limited number of studies on disciplinary effects in online education, the results of existing research are not yet conclusive.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Results of a study of a large number of web-based courses over a seven-year period suggest that student performance and satisfaction are significantly greater and withdrawal rates lower for courses with high-paradigm development than for courses with low-paradigm development. Even stronger relationships emerge when looking at the moderating effect of advanced versus introductory courses [31]. Hence, this educational approach appears especially conducive to virtual teams using the internet in advanced courses in a high-paradigm discipline (e.g., engineering).…”
Section: Implications For Curriculamentioning
confidence: 99%